2019
DOI: 10.11648/j.edu.20190803.14
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Status as Determinants of Students’ Performance in English Language in Secondary Schools in Tanzania

Abstract: This paper examined how parents' socio-economic status determined students' performance in English language in Tanzania secondary schools. Two research questions and two research objectives guided the study. The study was conducted in two randomly selected Regions in Tanzania Mainland. It employed a cross-sectional survey design to collect data from 350 students in sixteen secondary schools. Data was collected through a questionnaire and achievement tests and was analysed using both descriptive and inferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Muttaqin et al (2022) stated that SES significantly predicted academic achievements and English proficiency. Nyamubi (2019) in research conducted among secondary schools in Tanzania concluded that the regularity of English language usage at home and school enhanced performance in the English language together with encouragement as well as material and moral support. Nyamubi (2019) is also of the view that socioeconomic characteristics and their background in English language learning make an important factor in their learning outcomes.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Muttaqin et al (2022) stated that SES significantly predicted academic achievements and English proficiency. Nyamubi (2019) in research conducted among secondary schools in Tanzania concluded that the regularity of English language usage at home and school enhanced performance in the English language together with encouragement as well as material and moral support. Nyamubi (2019) is also of the view that socioeconomic characteristics and their background in English language learning make an important factor in their learning outcomes.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Nyamubi (2019) in research conducted among secondary schools in Tanzania concluded that the regularity of English language usage at home and school enhanced performance in the English language together with encouragement as well as material and moral support. Nyamubi (2019) is also of the view that socioeconomic characteristics and their background in English language learning make an important factor in their learning outcomes. Okunnuga and Christiana (2017) examined SES as a determinant of achievement in the English language in Nigeria and concluded that the SES of the parents had a positive influence on student's English language achievement.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%